TINJAUAN KUAT TEKAN DAN KANDUNGAN B3 TERLARUT DALAM BETON DENGAN AGREGAT BUATAN BERBAHAN DASAR BOTTOM ASH BATU BARA - Tohir, Abdul Rochman; Solikin, Mochamad; Purnama, Herry (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
Coal is an efficient fuel with stable heat production, so many industries use it as an energy source for the production and generation of electrical energy. Burning coal produces bottom ash waste in the combustion furnace and is categorized as B3 waste according to Government Regulation number 22 of 2021. This research is to create an alternative utilization and processing of coal bottom ash waste that is useful but still safe for the environment, namely by utilizing coal bottom ash in a ratio of 10% to 60% to sand plus cement as a binding material to form artificial aggregates, artificial aggregates are made into concrete mixtures. with a ratio of 1 cement: 2 sand and 3 artificial aggregates in the weight ratio of the materials. In this research, the maximum compressive strength value of concrete was obtained at f'c 13.89 (141.54 kg/cm2) at a ratio of 10% with a soaking time of 28 days, according to the maximum compressive strength value, coal bottom ash can be used as C quality concrete bricks. Leaching tests on 10 (ten) B3 parameters showed that Boron (B) compounds were detected above the quality standard, namely 27.62 mg/L in bottom ash, but the concentration decreased in artificial aggregates and was only 3.281 mg/L in concrete samples, while for other B3 compound parameters, the total concentration is below the specified quality standards.